An Extended Translation Service Portfolio in Research Translation - Klimkowski, Konrad (2022)
This article is a proposal to think about translation service portfolio in categories of contemporary service provision. As observed in the recent literature of the field, today’s services rely more and more on customisation, interactivity and relation-building. This article presents examples of opening a standard portfolio to opportunities identified by the translator through direct communication with the client. Benefits and limitations of such portfolio modifications are also discussed. The article is an invitation for the readers to rethink their portfolio strategies in search of competitive market advantages.
Keywords: translation as a service; Service-Dominant Logic; translation service portfolio; service customisation; research text translation